Point defect engineering study of phosphorus ion implanted germanium. Issue 1 (25th November 2013) - Razali, M. A.; Secchi, M.; Bersani, M.; Gwilliam, R. M.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract We present experimental results on shallow junction formation in germanium by phosphorus ion implantation and standard rapid thermal processing. An attempt is made to improve phosphorus electrical activation using point defect engineering method by introducing an excess of point defects in germanium prior to the phosphorus implantation. The focus is on studying the phosphorus activation and diffusion as a function of germanium co‐implant energy. Hall Effect and Secondary Ion Mass Spectrometry (SIMS) measurements are employed for characterisation of phosphorus activation and diffusion, respectively. Phosphorus activation was improved at higher annealing temperature for the implants with germanium co‐implant. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)